The Development of Mobile Learning Media for Excretion System Material for VIII Graders of SMPN 1 Taman Sidoarjo - Chrisdian, Viddo; Masitoh, Siti; Arianto, Fajar (International Journal for Educational and Vocational Studies, 2019)
The acceleration of 4.0 industrial revolution caused the development of digital era developed rapidly, therefore, learning resources can be accessed everwhere and everytime. Since the learning sources are easy to find,  the teachers are required to change the learning pattern into a learning facilitator that the focus is to give the appropriate learning resources for students based on their needs. According to the results of the interviews, there is a learning problem shows that the student learning outcomes in the excretion system material for class VIII SMP in SMPN 1 Taman Sidoarjo is still low. For this reason, it is necessary to develop a mobile learning media material excretion system that is feasibly and effectively used by students of VIII graders at SMPN 1 Taman Sidoarjo. The development model used is R&D Models from Walter Dick and Lou Carey.The data collection methods used were from questionnaire and test. Based on the trial results and data analysis, there are several conclusions, the results of the feasibility test of mobile learning media from the experts of material and media obtained a very good category.The individual trial obtained an excellent category, which is 90%, the percentgage of small group trials  is 90% and categorized as excellent, whereas the percentahe of the field trials is 89% and included in the excellent category. It can be concluded that the mobile learning media is suitable to use in the learning process. While the t-test with db = N - 1 = 33 - 1 = 32 and a significant level is 5%. Then the value of t table = 2.037 and tcount is 5.49. T arithmetic <t table (5.49> 2,037), therefore, the headway of media has been effective in improving student learning outcomes in class X of SMAN 1 Taman Sidoarjo on excretion system material.